An integrated system for voice command recognition and emergency detection based on audio signals. Issue 13 (1st August 2015) - Principi, Emanuele; Squartini, Stefano; Bonfigli, Roberto; Ferroni, Giacomo; Piazza, Francesco
Highlights Emergencies and home automation commands are recognised by means of acoustic signals. Distress calls are recognised to allow tele-assistance by a relative or a care giver. A novelty detection algorithm detects abnormal acoustic events. The entire system has been implemented in a low-consuming embedded platform.